Clinical and Economic Burden Associated with Prolonged Air Leaks Among Patients Undergoing Thoracic Resection: A Retrospective Database Analysis - Johnson BH; Johnston SS; Tewari P; Afolabi M; Danker W III (Dove Medical Press, 2023)
Barbara H Johnson,1 Stephen S Johnston,1 Pranjal Tewari,2 Mosadoluwa Afolabi,1 Walter Danker III3 1Epidemiology, Johnson & Johnson, New Brunswick, NJ, USA; 2Data Sciences, Mu Sigma, Bengaluru, Karnataka, India; 3Ethicon Franchise Health Economics and Market Access, Johnson & Johnson, Raritan, NJ, USACorrespondence: Barbara H Johnson, Real-World Data Analytics and Research, Epidemiology - MedTech, Johnson & Johnson, 410 George Street, New Brunswick, NJ, 08901, USA, Tel/Fax +1 603 616 6719, Email BJohns23@its.jnj.comPurpose: Prophylactic use of lung sealants among patients undergoing thoracic resection has been reported for the management of intraoperative air leaks and is associated with a lower incidence of prolonged air leak (PAL) and a shorter length of stay (LOS). This study estimated the incremental economic and clinical burden of PAL among patients with lung sealants used during thoracic resection in the United States.Patients and Methods: This retrospective analysis examined hospital data (Premier Healthcare Database) for adults (age ≥ 18 years) with inpatient thoracic resection between October 2015 - March 2021 (first admission=index) and lung sealant used during their procedure. Follow-up extended through 90 days post-discharge. Patients were grouped by presence/absence of PAL (ie, diagnosis of post-procedural air leak or post-procedural pneumothorax with associated LOS exceeding 5 days). Outcomes included intensive care unit (ICU) days, total index hospital costs, all-cause 30-, 60-, and 90-day readmission, discharge status, and in-hospital mortality. Generalized linear models quantified associations between PAL and outcomes, accounting for hospital-level clustering, and patient, procedure, and hospital/provider characteristics.Results: Among the 9727 patients included for study (51.0% female, 83.9% white, mean age 66 years), 12.5% had PAL, which was associated with significant incremental increases in ICU days (0.93 days, p< 0.001) and total hospital cost ($11,119, p< 0.001). PAL also decreased the likelihood of discharge to home (from 91.3% to 88.1%, p< 0.001) and increased the risk of readmission within 30, 60, and 90 days by up to 34.0% (from 9.3% to 12.6%;11.7% to 15.4%;13.6% to 17.2%, respectively), all p< 0.01. Absolute risk of mortality was low, but two times higher in patients with PAL versus those without PAL (2.4% vs 1.1%, p=0.001).Conclusion: This analysis demonstrates that despite the prophylactic use of lung sealants, PAL continues to put a burden on the healthcare system, highlighting an unmet need for improved sealant technology.Keywords: lung sealants, surgical complications, healthcare resource utilization, hospital costs